Musculoskeletal symptoms in patients with post-polio syndrome - Balzien, B.; Hofner, Benjamin; Harlander-Weikert, E.; Frommelt, P.; Bork, H.; Forst, Raimund; Fujak, A. (Zeitschrift für Orthopädie und Unfallchirurgie, 2014)
The prevalence of the post-polio syndrome (PPS) is in estimated 50 % of persons with established poliomyelitis with a subsequently stable phase of at least 15 years. The basic mechanism is a loss of motoneuron cells in the spinal cord resulting in muscle weakness and fatigue. In addition pain, cold intolerance and a loss of stamina are frequently reported. There are few studies focusing on the orthopaedic symptoms in the PPS. This study should support the health-care professionals to the address the needs of PPS patients.A questionnaire was developed to collect data on patients who have been diagnosed by a neurologist as fulfilling the criteria of a PPS. It consists of two parts. In the first part, general patient data are collected. In the second part, details of health, pain, and activities of daily living are collected at two points in time: the time of the stable phase immediately after the acute phase of the disease and the phase after the PPS diagnosis. The questionnaires were sent to patients with a diagnosis of PPS. A total of 124 questionnaires were analysed (male: 45, female: 79). Parts of the data were used to calculate a score. It was hypothesised that the score would demonstrate a higher load of orthopaedic symptoms in the PPS phase.The results show that the phase after poliomyelitis (stable phase vs. PPS phase) was associated with significantly different sum score relating to the orthopaedic impairments. The score in the stable phase is on average 18.6 units lower than that in the post-PPS diagnosis phase (p < 0.001). The hypothesis that in the PPS phase the load of orthopaedic symptoms is increased is confirmed by our data. The "loss of functioning in the upper extremity" is also significantly associated with the score (p = 0.004).At the time the survey was taken, patients reveal a high level of musculoskeletal impairments and disabilities after PPS than during the stable phase with regard to general health as well as pain status and performance of daily activities. Age has no significant impact. Many of the patients are severely limited, especially with regard to activities such as walking, climbing stairs, and performing simple household tasks. Since there is no causal therapy for the underlying degeneration of the anterior horn cell pools, treatment is focused on the compensation of the functional limitations.
EVALuna2:5477